Grounding religion : a field guide to the study of religion and ecology - Bauman, Whitney; Bohannon, Richard (Richard R.); O'Brien, Kevin J. (Kevin James), 1977- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Now in its third edition, Grounding Religion explores relationships between the environment and religious beliefs and practices. Established scholars introduce students to the ways religion shapes and is shaped by human-earth relations, surveying a series of key issues and questions with particular attention to issues of environmental degradation, social justice, ritual practices, and religious worldviews. Case studies, discussion questions, and further readings enrich students' experience. This third edition features updated content, including revisions of every chapter and new material on religion and the environmental humanities, sexuality and queer studies, class, ability, privilege and power, environmental justice, extinction, biodiversity, and politics. An excellent text for undergraduates and graduates alike, it offers an expansive overview of the academic field of religion and ecology as it has emerged in the past fifty years and continues to develop today"--
Includes bibliographical references and index.
Keywords: Human ecology -- Religious aspects